Intervensi Cold Pack Terhadap Intensitas Nyeri Pasien Pasca Prosedur Kateterisasi Jantung - Dhivenka Perwita Putri, Riska; Irawan AM, Ady; Rahmasari, Ikrima (Pustaka Galeri Mandiri, 2026)
Pain is a common side effect experienced by patients after undergoing cardiac catheterization procedures, primarily caused by trauma to the vascular tissue at the catheter insertion site. To address this issue, a non-pharmacological intervention that is easy to apply, safe, and effective is the use of cold pack therapy, which works by inducing vasoconstriction and inhibiting the transmission of pain impulses through nerve fibers, thereby reducing pain perception. This study aimed to determine the effect of cold pack application on pain intensity in post-cardiac catheterization patients at Dr. Moewardi General Hospital, Surakarta. This study used a quasi-experimental design with a pretest-posttest control group approach, involving 46 respondents selected using accidental sampling technique. The respondents were evenly divided into two groups of 23: the intervention group received cold pack therapy, while the control group received standard care. The measurement instruments used were the Numeric Rating Scale (NRS) and an observation sheet. Data were analyzed using the Wilcoxon Signed Rank Test and the Mann-Whitney U Test. The Wilcoxon test showed a significant change in pain intensity in the intervention group before and after the application of cold pack (p = 0.000). In addition, the Mann-Whitney test showed a significant posttest difference between the intervention and control groups (p = 0.000). The results indicate that cold pack therapy is proven effective in reducing pain in post-cardiac catheterization patients and can be implemented as part of non-pharmacological nursing interventions in the management of pain after invasive procedures.